Penggunaan Model Problem Based Learning Dalam Meningkatkan Minat Dan Motivasi Belajar Peserta Didik Pada Mata Pelajaran IPAS Di Kelas IV Sekolah Dasar - Aprilia, Yustika; Asrin; Zulfikri, Bilyadi (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
This research aims to determine the influence and success of using the Problem Based Learning model in increasing students' interest and learning motivation in grade IV elementary school science subjects. This type of research is Classroom Action Research (PTK). The subjects of this research were class IV/A students. The data collection technique used by researchers in this action is a qualitative technique obtained from observations of students during the action process. The qualitative data obtained by researchers in this action is used to explain the results of observations made by researchers as observers. Furthermore, the instruments used by researchers are observation sheets and field notes. The results of this research showed that the average percentage of students' interest and learning motivation was as follows, cycle I was 51.3% and cycle II was 84%. From these data it can be concluded that there is an increase in students' interest and motivation to learn through the problem based learning (PBL) learning model.